2009
DOI: 10.1590/s0004-282x2009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body image and self-concept and their correlation with depressive symptoms in Parkinson's disease

Abstract: Avaliação da imagem corporal, autoconceito e suas correlações com os sintomas depressivos na doença de ParkinsonResumo -Objetivo: Identificar características de imagem corporal e autoconceito em indivíduos com doença de Parkinson (DP) acima de cinqüenta anos de idade. os objetivos secundários são analisar se a imagem corporal e o autoconceito são influenciados pela gravidade da DP e, verificar se existe correlação entre depressão, autoconceito e imagem corporal na DP. Método: Participaram do estudo 48 indivídu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
(21 reference statements)
1
13
0
8
Order By: Relevance
“…These results were in line with the misperception of body image showed for subjects affected by PD (Gamarra et al, 2009). This misperception was also found related to depressive symptoms, and this relationship, together with the reduction of pain, can explain the positive effects of our treatment also on depression.…”
Section: Discussionsupporting
confidence: 89%
“…These results were in line with the misperception of body image showed for subjects affected by PD (Gamarra et al, 2009). This misperception was also found related to depressive symptoms, and this relationship, together with the reduction of pain, can explain the positive effects of our treatment also on depression.…”
Section: Discussionsupporting
confidence: 89%
“…A avaliação da imagem corporal em indivíduos com DP foi realizada por poucos estudos na literatura 12,13 , que utilizaram questionários e escalas não específicos e não validados para essa população, como: TAPS ( Observou-se na literatura relatos de que indivíduos com DP apresentam alteração da percepção da imagem postural, principalmente relacionadas ao plano frontal 8,14 . Entretanto, apesar da literatura sinalizar para essa alteração de percepção corporal em idosos com DP, não foram encontradas propostas de medidas de avaliação específicas relacionadas à imagem postural, em virtude, possivelmente, do caráter subjetivo que envolve a percepção individual da organização da postura.…”
Section: Métodosunclassified
“…corporal, além disso, ainda são poucos os estudos 12,13 que realizaram essa avaliação, especificamente em indivíduos com DP.…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation
“…As cognitive impairments are among the common characteristics of PD (De Pandis et al, ; Levin et al, ), this test is suitable for people with PD and is commonly used for PD screening (De Pandis et al, ; Pinto & Peters, ). As people with PD may also exhibit with a distorted body schema (Gamarra et al, ; Sandyk, ), and given that drawing tests can not only reflect cognitive and motor status but also how the stereotypical image of a drawn object is represented in the mind (Anderson, ; Zoltan, Siev, & Freishtat, ); the drawing of a body or its parts may be helpful in evaluating a specific aspect of cognitive status–body schema (Freund, Gravenstein, Ferris, Burke, & Shaheen, ; Moseley, ) in people with PD (Sandyk, ). Although not thoroughly investigated to date, it has been suggested that PD characteristics play a role in body schema misperceptions, and thus potentially exhibited in drawings (Bissolotti et al, ).…”
Section: Introductionmentioning
confidence: 99%